2020
DOI: 10.3390/vaccines8040675
|View full text |Cite
|
Sign up to set email alerts
|

Association between Exposure to Influenza Vaccination and COVID-19 Diagnosis and Outcomes

Abstract: We explored whether influenza vaccination (IV) affects susceptibility to SARS-CoV-2 infection and clinical outcomes in COVID-19 patients in 17,608 residents of the Italian province of Reggio Emilia undergoing a SARS-CoV-2 test. Exposure to IV was ascertained and the strength of the association with SARS-CoV-2 positivity expressed with odds ratios (OR). Rates of hospitalisations and death in those found positive were assessed and hazard ratios (HR) were estimated. The prevalence of IV was 34.3% in the 4885 SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
52
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 30 publications
12
52
2
3
Order By: Relevance
“…This is a slight contradiction to a recent report from Italy demonstrating the greatest protection against COVID-19 in elderly patients who received the vaccine in close proximity to COVID-19 exposure as compared to several months before. 14 While we did see decreased mortality in the influenza vaccinated group, the association was non-significant. This may be due to a small sample size and the low number of deaths observed.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This is a slight contradiction to a recent report from Italy demonstrating the greatest protection against COVID-19 in elderly patients who received the vaccine in close proximity to COVID-19 exposure as compared to several months before. 14 While we did see decreased mortality in the influenza vaccinated group, the association was non-significant. This may be due to a small sample size and the low number of deaths observed.…”
Section: Discussionmentioning
confidence: 53%
“…Recent studies have suggested that prior vaccination to pathogens such as tuberculosis and influenza may confer some protection against COVID-19. 9 , 10 , 11 , 12 , 13 , 14 An analysis of over 92,000 COVID-19 patients in a non-peer reviewed study from Brazil found a 17% reduced odds of mortality, 8% lower odds of need for intensive care treatment and 18% lower odds of invasive respiratory support in those who received an influenza vaccine. 12 Separate epidemiologic studies in Italy and the United States found a correlation between increased vaccination rates in those aged greater than 65 years and decreased rates of COVID-19 deaths across different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in an epidemiological study performed on an Italian population, the flu vaccine was associated with reduced susceptibility to COVID-19. However, in this study, the death rate was affected by flu vaccination only in a small group of patients who received the vaccine in the period immediately preceding the onset of the outbreak [11]. In our study, we only included symptomatic patients who presented themselves to the Emergency Department.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized pathophysiological mechanisms underlying the interaction between influenza vaccine and coronavirus infection are structural similarities in ligands for cell receptors, antibody cross-reactivity, and a non-specific cell-mediated response [4,[7][8][9]. Several authors have studied the effect 1 3 of influenza (flu) and pneumococcal vaccination on the susceptibility and mortality of COVID-19, with conflicting results [10,11]. This is why we have designed a study aimed at verifying whether influenza vaccination may influence the clinical course of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…7 Additionally, ecological studies correlating influenza vaccination uptake rates and COVID-19 mortality, published in scientific journals as articles or rapid responses to articles sustain these hypotheses. 8,9 Conversely, several articles have been published in scientific journals on the negative association or no association between influenza vaccination and COVID-19 mortality, hospitalisation and infection, 10,11 many of which are summarised in a recent systematic literature review. [12][13][14][15] The authors of the latter paper recommend that further studies are carried out to validate these preliminary findings across settings.…”
Section: Introductionmentioning
confidence: 99%